PEMBENTUKAN PROVINSI KALIMANTAN UTARA (1999-2012) - Joshua Jolly Sucanta Cakranegara (Balai Pelestarian Nilai Budaya Kalimantan Barat, 2020)
North Kalimantan Province (Kaltara) is the 34th province or the youngest province inIndonesia. The establishment of the province is inseparable from long historical dynamics.This can be seen from the period of the establishment of the Bulungan Sultanate, the DutchEast Indies colonial government, the Japanese occupation government, until the Indonesiangovernment. By applying historical approach, this paper aims to explain the historicaldynamics of the establishment of North Kalimantan Province after 1998, since regionalautonomy strengthened in 1999 through Law Number 22 of 1999 on Regional Governmentto the final establishment through Law Number 20 of 2012 on Establishment of NorthKalimantan Province. The results of this study indicate that the establishment of the provincecannot be separated from the spirit of regional autonomy that was intensified after 1998.In addition, a number of multidimensional studies in the social-economic, natural resourcemanagement, defense-security, and territorial fields have become a strong foundation forthe establishment of the province. Thus, political processes, both at the central and regionallevels, as well as in-depth study and great local community support were key factors in theestablishment of North Kalimantan Province. This become a historical dynamic in thehistory of regional government in the Unitary State of the Republic of Indonesia (NKRI).